Venture capitalists' involvement in their investments: Extent and performance - Macmillan, Ian C.; Kulow, David M.; Khoylian, Roubina (Journal of Business Venturing, 1989)
Venture capitalists responded to a questionnaire that asked them to identify their degree of involvement in a number of activities for a funded venture as well as other characteristics of the venture, including its performance. The three-page questionnaire was distributed to a sample of 350 venture capitalists during December 1986 and February 1987. In all, 62 questionnaires (18%) were completed and returned. The results indicated that venture capitalists were involved most—compared to the entrepreneur—in the financial aspects of the venture. The activity that had the highest degree of involvement was serving as a sounding board to the entrepreneur. The lowest degree of involvement occurred in those activities concerning the ongoing operations. Factor analysis on involvement patterns in the venture activities identified four distinct areas of involvement: development and operations, management selection, personnel management, and financial participation. The venture capitalists indicated that if they could change their degree of involvement, overall they would have done so only slightly. It was evident, however, that they would have increased their involvement in those activities requiring a minimal time commitment, such as formulating business strategy or marketing plans, or serving as a sounding board to the entrepreneur. It was evident that they would have decreased their involvement in activities that required substantial time commitment, such as developing production or service techniques, selecting vendors and equipment, or soliciting customers or distributors. Perhaps the most important result was the identification of three distinct levels of involvement adopted by venture capitalists: 1) Laissez Faire involvement, in which the venture capitalists exhibited limited involvement; 2) Moderate involvement, in which venture capitalists exhibited moderate involvement; and 3) Close Tracker involvement, in which venture capitalists exhibited more involvement than the entrepreneur in a majority of the identified activities. Because tests regarding the venture firms, the products or services in relation to the market, and management team characteristics did not significantly explain why the three distinct types of venture capitalist involvement emerged, it appears that venture capitalists exhibited different involvement levels solely because they elected to do so. Tests also indicated that the difference in the performance level of the ventures among the three groups was statistically insignificant. Regression analyses indicated that for each of the three types of involvement, involvement in various activities had different correlations with performance. Among Laissez Faire involvement ventures, developing the professional support group had a positive correlation with venture performance. Among Moderate involvement ventures, monitoring operations had a positive correlation with venture performance while involvement at the strategic level and in searching for management candidates exhibited negative correlations. Finally, among Close Tracker involvement ventures, negotiating employment terms with management had a positive correlation with performance, while searching for management candidates exhibited a negative correlation. It is interesting that searching for management candidates in both the Moderate and Close Tracker ventures had a negative correlation with venture performance. These results are important because they show that depending on the involvement types selected by venture capitalists, different involvement strategies in the various activities should be more suitable. If venture capitalists recognize this they can adopt more appropriate strategies, which may lead to more successful ventures.